Genome-wide identification of the pectate lyase (PEL) gene family members in Malvaceae, and their contribution to cotton fiber quality - Qian Deng; Zeyu Dong; Zequan Chen; Zhuolin Shi; Ting Zhao; Xueying Guan; Yan Hu; Lei Fang (Journal of Integrative Agriculture, 2024)
Pectin is a major constituent of the plant cell wall. Pectate lyase (PEL, EC 4.2.2.2) uses anti-β-elimination chemistry to cleave the α-1,4 glycosidic linkage in the homogalacturonan region of pectin. However, limited information is available on the comprehensive and evolutionary analysis of PELs in the Malvaceae. In this study, we identified 597 PEL genes from 10 Malvaceae species. Phylogenetic and motif analyses revealed that these PELs are classified into six subfamilies: Clades I, II, III, IV, Va, and Vb. The two largest subfamilies, Clades I and II, contained 237 and 222 PEL members, respectively. The members of Clades Va and Vb only contained four or five motifs, far fewer than the other subfamilies. Gene duplication analysis showed that segmental duplication played a crucial role in the expansion of the PEL gene family in Gossypium species. The PELs from Clades I, IV, Va, and Vb were expressed during the fiber elongation stage, but nearly all PEL genes from Clades II and III showed no expression in any of the investigated fiber developmental stages. We further performed single-gene haplotype association analysis in 2,001 G. hirsutum accessions and 229 G. barbadense accessions. Interestingly, 14 PELs were significantly associated with fiber length and strength traits in G. barbadense with superior fiber quality, while only eight GhPEL genes were found to be significantly associated with fiber quality traits in G. hirsutum. Our findings provide important information for further evolutionary and functional research on the PEL gene family members and their potential use for fiber quality improvement in cotton.